Tekist á við tíðarhvörf : um líðan og afstöðu 47 til 53 ára kvenna til tíðarhvarfa og notkunar tíðarhvarfahormóna - Herdís Sveinsdóttir (2005)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Background: The unexpected findings of the WHI-study, made public in July 2002, showed that the risk of using combined hormone therapy (HT) exceeded its benefits. This complicated women’s decision making about whether to use HT or not and makes it important to study the determinants of women’s attitudes to HT. Aim: This study sought to illuminate what influences women’s decisions about HT, describe the extent and source of menopausal education, symptom experience, health and lifestyle, knowledge about the findings of the WHI-study and attitudes towards HT and towards menopause. Methods: A self-administered questionnaire based on dichotomous questions, multiple choice questions and questions on attitudes, was mailed to 1000 women randomly selected from the National Registry of Iceland. Response rate was56%. Findings: 252 participants had used HT and 46% had stopped its use. Younger women were less likely to use HT. The reasons given for HT use were mostly symptom management. Older women and users of HT held more positive view towards HT than the comparison groups. However, never HT users held more positive attitudes towards menopause than users. 51% of participants received adequate menopausal education while 84% stated that the health authorities should provide more menopausal education. Major source of menopausal education was media and female friends. The participants discussed use of HT mostly with a physician. 65% had heard about the WHI-study and the findings influenced the decision of a large proportion of HT users as well as women intending to use HT about whether to continue, stop, or start using HT. Conclusion: Perimenopausal Icelandic women have stopped or are considering to stop using HT due to the findings of the WHI-study. They also want more menopausal education provided by the health authorities. Physicians are very influential in their decision making regarding HT use. Bakgrunnur: Notkun ...